Identidades em construção: um olhar sobre a futebolização da juventude no ensino médio - Koch, Rodrigo (2018)
This doctoral thesis was elaborated in the Graduate Program in Education, Federal University of Santa Maria, in the line of research II: School Practices and Public Policies, having as a theme thematic High School: Curriculum and Juvenile Cultures. The research was based on the researcher's questioning based on the confirmation of a certain footballization of the culture, and the strong presence of this phenomenon among the youths in High School, also expressing itself in the everyday spaces of life. The objective was to understand the contemporary process of footballization and how it relates to the construction of juvenile identities in the public and private schools of the High School Hortensias Region. There is a cultural pedagogy under way related to soccer. Dialogue with Portuguese, French, Latin American, British and Brazilian researchers (João Nuno Coelho, José Machado Pais, Gilles Lipovetsky, Guy Debord, Michel Maffesoli, Pablo Alabarces, Sérgio Fiengo, Nestor Garcia Canclini, Rossana Reguillo, Beatriz Sarlo, Franklin Foer , Richard Giulianotti, Simon Kuper, Stefan Szymanski, Lucia Rabello de Castro, Juarez Dayrell, Luiz Henrique de Toledo and Hilário Franco Júnior among others) presents a panorama on the footballization of contemporary culture, and postmodern youth and youth cultures and its links with education. It was also used the theoretical reference of authors who have subsidized the Cultural Studies, among them Stuart Hall and Zygmunt Bauman, to characterize identity, globalization, postmodern condition and consumption. With observations, image records, interviews and informal conversations in schools of the Hortensias Region (cities of Canela, Gramado and São Francisco de Paula), the pedagogical marks of the footballization of culture were analyzed and analyzed, constructed in the most varied contexts such as media, families, groups and communities, among others, and that have repercussions on the school environment. The analysis seeks to show what footballization produces in school, in the curriculum and in the identity fragments of youths, pointing to different manifestations such as clothing, accessories and behaviors, among others. Young people acquire these footballed brands already in the cradle, and transform them during their life trajectories, constructing their identities, in a liquid, light and 'flaneur' condition. Postmodern football, extremely mediatized and spectacular, constantly produces new identities. The study indicates productivity of soccer in communities with strong ties and brands of this modality.